In Favor Of An Immigration Data Protection Law In Indonesia And Its Utilization For Contact Tracing - Jihyun Park; Dodik Setiawan Nur Heriyanto (Prophetic Law Review, 2022)
Immigration data form a substantial part of the border protection between countries. However, the quality and integrity of each country’s immigration data varies greatly in terms of technology and regulation. A country that has a weak a legal framework on data protection has proven to be easily abused by irresponsible parties. Including when Indonesia tries to carry out tracing by synchronizing the data in the Peduli Lindungi application with immigration data, there will be a potential violation of the privacy rights of individuals. Hence, this study applies a normative and empirical (mix) legal research methodology to analyze two keys issues: what are the advantages of synchronizing the domestic tracing application called Peduli Lindungi to the immigration data? and what kind of legal framework to prevent the misuse of personal data in Indonesia? With regulatory and comparative approaches, this study concludes without powerful legal framework, there will be no legal assurance to the promotion of privacy rights in the synchronization and the use of immigration data for health tracing purposes. From the empirical side, Indonesian’s current policy does not enable monitoring or evaluating authority to scrutinize ministerial activities in collecting and utilizing personal data. Moreover, by considering several problems of data breach in Indonesia, a single and unified data protection law is needed to integrate and provide uniformity of implementation for data protection.Keywords: data protection law, immigration, privacy rights. Mendukung Undang-Undang Perlindungan Data Keimigrasian Di Indonesia Dan Pemanfaatannya Untuk Pelacakan Kontak Abstrak Data imigrasi merupakan bagian penting dari perlindungan perbatasan antar negara. Namun, kualitas dan integritas data keimigrasian masing-masing negara sangat bervariasi dari segi teknologi dan regulasi. Negara yang memiliki kerangka hukum perlindungan data yang lemah terbukti mudah disalahgunakan oleh pihak-pihak yang tidak bertanggung jawab. Termasuk ketika Indonesia mencoba melakukan tracing dengan menyinkronkan data pada aplikasi Peduli Lindungi dengan data keimigrasian, maka akan berpotensi terjadi pelanggaran terhadap hak privasi individu. Oleh karena itu, penelitian ini menggunakan metodologi penelitian hukum normatif dan empiris (campuran) untuk menganalisis dua masalah utama: apa keuntungan dari sinkronisasi aplikasi penelusuran dalam negeri bernama Peduli Lindungi terhadap data keimigrasian? dan apa kerangka hukum untuk mencegah penyalahgunaan data pribadi di Indonesia? Dengan pendekatan regulasi dan komparatif, studi ini menyimpulkan tanpa kerangka hukum yang kuat, tidak akan ada jaminan hukum untuk promosi hak privasi dalam sinkronisasi dan penggunaan data imigrasi untuk tujuan penelusuran kesehatan. Dari sisi empiris, kebijakan Indonesia saat ini tidak memungkinkan kewenangan pemantauan atau evaluasi untuk meneliti kegiatan kementerian dalam mengumpulkan dan memanfaatkan data pribadi. Selain itu, dengan mempertimbangkan beberapa masalah pelanggaran data di Indonesia, diperlukan undang-undang perlindungan data yang tunggal dan terpadu untuk mengintegrasikan dan memberikan keseragaman implementasi perlindungan data.Kata kunci: undang-undang perlindungan data, keimigrasian, hak privasi.